Predictive factors of disordered eating among adolescents in Bosnia and Herzegovina - Martina Krešic Coric; Mirjana Graovac; Nikolina Pravdić; Ana Boban Raguž; Ana Kaštelan (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Due to excessive concerns and focus on weight control and body shape, adolescents often resort to inappropriate behaviours and attitudes towards eating, resulting in physical and psychological issues. This study aimed to assess possible relationships and predictor variables between disordered eating and age, BMI, body appreciation, self-esteem, quality of family interactions, psychosocial health and childhood trauma experience in adolescents of both sexes in the city of Mostar (Bosnia and Herzegovina). MATERIALS AND METHODS: A cross-sectional study was carried out on a suitable sample of 724 high-school students aged 14-19 years. The following tools have been used: socio-demographic questionnaire, The Eating Attitudes Test (EAT-26), Body Mass Index (BMI), Body Appreciation Scale (BAS), Rosenberg's Self-Esteem Scale, Quality of Family Interaction Scale (KOBI), and Paediatric Quality of Life Inventory, version 4.0 (PedsQLTM) and Childhood trauma Questionnaire (CTQ). Collected data were analyzed in SPSS v. 20.0 software using Pearson's correlation coefficient and multiple regression analysis. RESULTS: Body appreciation is the most significant predictor for developing disordered eating across the entire sample of adolescents (β = -0.325, P < 0.05) and individually for male adolescents (β = -0.199, P = 0.010) and female adolescents (β = -0.379, P < 0.001). In addition to this variable, BMI has proved to be a statistically significant predictor in explaining the eating behaviours of female adolescents (β = 0.185, P < 0.001), while this happens to be self-esteem for male adolescents (β = -0.211, P < 0.022). CONCLUSION: The most significant risk factors for developing disordered eating in adolescents are body appreciation, BMI and self-esteem. Results of this research can contribute to enhancement of intervention programmes which promote a positive body image and aim to prevent disordered eating in adolescents of both sexes.